1974
DOI: 10.1159/000122581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Hydrocortisone on Corticosteroid Circadian Periodicity, Responsiveness to ACTH and Stress in Prepuberal and Adult Rats

Abstract: 500 µg hydrocortisone acetate was administered subcutaneously to 2-day-old male and female rats. Study of these animals at 30 days of age revealed virtual obliteration of the circadian periodicity of plasma corticosteroid levels, but preservation of normal adrenal responsiveness to ACTH and to the stresses of immobilization and etherization. Circadian periodicity was normal in both male and female animals studied at 80 days of age. The other cited parameters were tested only in male animals at this age, and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…The data show further that the ACTH response to stress is suppressed in a dose-dependent fash ion, the greater suppression occurring in ani mals treated with the larger dosage. While we did not measure corticosterone levels through out the period following the neonatal hydro cortisone injection on day 1, Krieger [13] re ported that 0.5 mg of hydrocortisone admin istered on day 2 elevated plasma corticoste rone levels above that of saline-injected con trols for 48 h. The present effects may be the result of varying lengths of exposure to hydro cortisone resulting from differential rates of clearance at each dosage level. None of the doses of hydrocortisone appeared to abolish completely the release of ACTH following stress, since stress levels in all animals were elevated over baseline values of untreated con trols.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The data show further that the ACTH response to stress is suppressed in a dose-dependent fash ion, the greater suppression occurring in ani mals treated with the larger dosage. While we did not measure corticosterone levels through out the period following the neonatal hydro cortisone injection on day 1, Krieger [13] re ported that 0.5 mg of hydrocortisone admin istered on day 2 elevated plasma corticoste rone levels above that of saline-injected con trols for 48 h. The present effects may be the result of varying lengths of exposure to hydro cortisone resulting from differential rates of clearance at each dosage level. None of the doses of hydrocortisone appeared to abolish completely the release of ACTH following stress, since stress levels in all animals were elevated over baseline values of untreated con trols.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have reported increased adrenal weights (mg/ 100 g b.w.) in hydrocortisone-treated animals [13,21], and either decreased [13,29] or in creased [13] adrenal response to stress or ACTH. The site of the CNS-pituitary-adrenal lesion in steroid-treated animals has not been determined.…”
mentioning
confidence: 92%
See 3 more Smart Citations